2016
DOI: 10.1186/s41016-015-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinal cord oligodendroglioma: a case report and review of the literature

Abstract: Background: Primary spinal cord oligodendroglioma is extremely rare. In an extensive review of this disease, 53 cases were reported. Furthermore, the authors summarize the characteristics of the primary spinal cord oligodendroglioma; chronological presentation , neurological imaging, treatment and the outcome obtained in the present case as well as review the literature. Case Presentation: A 46-year-old male who had progressive neck pain for a year. Magnetic resonance imaging showed an intramedullary mass from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Although IM spinal cord tumors appear more frequently in pediatric than adult patients, adult PSOs are more common than pediatric PSOs. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 45 46 47 48 49 ] The clinical presentation of a PSO is similar to that of other IM spinal tumors, i.e., PSOs do not present with unique characteristic. PSO symptoms depend mostly on the anatomical site of the tumor and usually develop over a period spanning months to years.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Although IM spinal cord tumors appear more frequently in pediatric than adult patients, adult PSOs are more common than pediatric PSOs. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 45 46 47 48 49 ] The clinical presentation of a PSO is similar to that of other IM spinal tumors, i.e., PSOs do not present with unique characteristic. PSO symptoms depend mostly on the anatomical site of the tumor and usually develop over a period spanning months to years.…”
Section: Discussionmentioning
confidence: 96%
“…[ 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] With the latest publications, including a few mini-clinical series and cases, the total number of reported cases of PSO is 60. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 ] Fortuna et al . found that PSO cases were equally distributed between both sexes and the literature to date indicates no significant sex predilection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations